TA'AWUN DALAM PANDEMI - Afita Nur Hayati (Institut Agama Islam Negeri (IAIN) Ponorogo, 2021)
In Islam, ta’awun concept as mutual help, has been arranged clearly at Al-Qur’an. Pandemic corona virus makes impact in society that need real contribution from ta’awun concept. This article narrates how Aisyiyah leaders at East Kalimantan from district to district implement Gerakan Ta’awun Tahun 2020 as one of real form of practice Al-Maun theology, with three pilars of activities i.e. health services, education, and social services. With naturalistic qualitative to understanding from inner perspective as method of this research, this article also describes resilience of families that supported with ta’awun. Datas taken through interview with lead of media support of Aisyiyah East Kalimantan leaders, observations and secondary sources. Lenting community establish at pandemic situation as part of food security for families. Synergizing all asemblies at Aisyiyah East Kalimantan continue to play an active role in handling, preventing the spread of the corona virus based on family and community, as a form of social piety.